Moodcafe : from idea conception to raising funds - Singla, Chitra; Sethuram, Shridhar; Jena, Sanjay K. (London : Indian Institute of Management, Ahmedabad, 2024)
The case describes a situation facing Mikul Patel and Rahul Mirdha, the co-founders of Moodcafe, an online mental healthcare service provider. They had to choose between the two angel investors and negotiate the terms and conditions for funding their start-up. In September 2018, they started Moodcafe to provide services to people struggling with mental health issues. The case mentions several crucial decisions in a start-up’s journey that are related to "minimum viable product", "adding more features to the platform", "proof-of-concept testing of the product in the market", "building a core team" and "deciding on equity division between the co-founders". The co-founders need to raise funds from angel investors to test the product at the country level. They need to choose between the two angel investors and decide the terms and conditions of seeking investment.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Investments -- Case studies; Community mental health services -- Case studies